Immobilized Palladium Nanoparticles on Phosphanamine-grafted Cellulose for Arylation of Uracil - Yang, Qian; Ma, Na; He, Yangqing; Yu, Xiaojiao; Yao, Binghua (Current Organocatalysis, 2022)
Background: The synthesis of 5-arylation uracil nucleosides is an imperative challenge, especially for the method of Suzuki reaction using N-unprotected uracil as materials, which holds the potential to enhance the yield. Objective: The objective of this study was to find a more efficient catalyst to increase the yield of aryluracils and aryluridines. Methods: We first constructed the Phosphanamine-Grafted Cellulose (PAGC) from cellulose material. Then the nanocatalyst PAGC/Pd(0) was prepared through heating and reducing the mixture of PAGC and Pa(OAc)2. Results: When using this nanocatalyst to catalyze the Suzuki reaction of 5-iodouracil or 5-iodouridine and aryl heterocyclic boronic acids, the arylation yields have been significantly improved. Conclusion: This means that the resultant nanocatalyst exhibits a remarkable catalytic efficacy for Suzuki arylation of 5-iodouracil and 5-iodouridine.
Keywords: Palladium nanocatalyst